Pattern of Allergen Sensitization in Patients with Allergic Rhinitis: A Hospital-Based Observational Study - Seema Monga; Ratna Priya; Deepti Agarwal; Girisha Vats; Insha Jauhar (International Journal of Science and Healthcare Research, 2026)
Background: Allergic rhinitis is a common immunoglobulin E (IgE)-mediated inflammatory disorder characterized by nasal symptoms triggered by exposure to environmental allergens. The pattern of allergen sensitization varies according to geographical and environmental factors, and identification of predominant allergens is essential for effective allergen avoidance strategies and individualized management. Objective: To evaluate the pattern of allergen sensitization among patients with allergic rhinitis attending a tertiary care teaching hospital in Northern India. Methods: This hospital-based observational study was conducted in the Department of Otorhinolaryngology over a two-year period (October 2022–June 2024) following institutional ethics committee approval. Sixty-four patients aged 18–55 years with allergic rhinitis diagnosed according to Allergic Rhinitis and its Impact on Asthma (ARIA) guidelines were included. Allergen sensitization was assessed using skin prick testing and/or serum allergen-specific IgE testing. A standardized allergen panel comprising house dust mites, pollens, fungi, dusts, and cockroach allergens was evaluated. Data were analyzed using descriptive statistics and expressed as frequencies and percentages. Results: The study included 38 (59.4%) males and 26 (40.6%) females, with a mean age of 31.8 years. Dermatophagoides farinae was the most frequently identified allergen, with sensitization observed in 23 (35.9%) patients. Other commonly identified allergens included Chenopodium album, Aspergillus fumigatus, hay dust, house dust, Cassia fistula, cement dust, and Candida albicans. Sensitization to multiple allergens was common, with 36 (56.3%) patients demonstrating polysensitization to four or more allergens, while only 12 (18.8%) exhibited mono- or paucisensitization. Conclusions: House dust mites, particularly Dermatophagoides farinae, were the predominant sensitizing allergens among patients with allergic rhinitis in this population. The high prevalence of polysensitization highlights the importance of comprehensive allergen evaluation to facilitate targeted environmental control measures and support individualized management, including consideration of allergen-specific immunotherapy where appropriate. Keywords: Allergic Rhinitis; Hypersensitivity, Immediate; Skin Tests; Mites; Immunoglobulin E; Allergens.